Strategies for enhancing yield and quality of forage-grain dual-purpose ratoon rice: role of first-season density and nitrogen management - Yuyuan Ouyang; Yuyuan Ouyang; Guangyi Chen; Chuntao Yang; Conghua Zhu; Li Zhang; Wei Li; Hong Yang; Ziyu Li; Yao Zhang; Junqi Yu; Xi Luo; et al. (Frontiers in Plant Science)
The “forage-grain dual-purpose” model helps ease land-use competition and supports high-yield, high-quality rice production. However, integrated strategies to simultaneously improve silage rice and ratoon rice yield and quality across both seasons require further systematic study. A two-year field study (2022–2023) was conducted using two widely cultivated indica hybrid rice cultivars, F You 498 (FY498) and Chuankangyou Simiao (CKYSM), in Southwest China. Treatments included three planting densities (D1: 16.7 × 104; D2: 20.8 × 104; D3: 27.8 × 104 hills ha−1) and three nitrogen levels (N1: 150; N2: 225; N3: 300 kg ha−1) in the first season. Results showed that: Silage yield increased significantly with higher density and nitrogen input. FY498 reached the highest yield under D3N3 (48.46-57.60 t ha−1), while CKYSM performed best under D2N3 (45.39-50.93 t ha−1). Elevated density and nitrogen levels increased acid detergent fiber and neutral detergent fiber contents and reduced starch, indicating a decline in overall silage quality, though crude protein improved. Within the studied parameters, nitrogen application had a more pronounced influence on silage quality compared to planting density. Relative feed value was highest under D1N1 or D1N2, meeting national Grade II silage standards. In the ratoon season, increased density and nitrogen enhanced aboveground biomass, SPAD values, panicle number, and actual yield. However, higher density reduced leaf area index, and excess nitrogen decreased seed setting rate and 1000-grain weight. Maximum actual yields were observed under D2N3 or D3N2: FY498 (7.71-9.61 t ha−1) and CKYSM (6.49-9.00 t ha−1). Nitrogen application improved milling quality to some extent, while higher density negatively affected it. Both factors reduced appearance quality and RVA characteristics. Nutritional and safety quality varied significantly across treatments and cultivars. FY498 had high protein and low cadmium content under D1N3; CKYSM showed high starch and low cadmium under D2N3, indicating superior overall performance. In summary, D1N1 produced better silage and rice quality but lower yield. For higher overall productivity and safety, FY498 with D3N3 and CKYSM with D2N3 were optimal, despite moderate declines in quality traits. This new cultivation method may provide a beneficial option to balance silage rice and ratoon rice yield and quality.